Tributaries of the authoritarian phenomenon in the Arab region: between cultural justifications and the deposits of crisis religious heritage - Fouka, Sofiane (Journal of Human Sciences, 2022)
Authoritarianism is a characteristic of Arab political life and constitutes a specific model of relations within society. Arab culture has been criticized for assuming an important part of the responsibility for establishing and perpetuating tyranny. With some of these values it makes the individual ready to accept and coexist with despotism, which allows regimes to easily take the path of authoritarianism as long as Arab culture - despite what it has brought to the humanity - has not been freed from the sediments attached to it from its heritage; also the religious discourse based on fanaticism and which reject the formula of the national state has in turn complicated the Arab situation, and it has thus become essential that the positive side of this culture corrects the situation.